The Corelation of Exclusive Breastfeeding with Nutritional Status in Babies Age 6-24 Months at the Kedungsari Health Center, Mojokerto Regency - sukma sahadewa; Nike Salindri; Sandra Miladyna; Siti Hadijah (Universitas Wijaya Kusuma Surabaya, 2021)
The objectives of this research is to find out the prevalence of exclusive breastfeeding, nutritional status, and the correlation between of breastfeeding and nutritional status in babies aged 6 to 24 months at the Kedungsari Public Health Center in Mojokerto Regency. This study used 50 babies aged 6-24 months from the Kedungsari Health Center as samples. This study applied a cross-sectional study design. The data was collected by gathering primary data via questionnaires and secondary data from the Kedungsari Health Center. The majority of the children in this research, aged 6-24 months, had been exclusively breastfed (58%). The majority of the children in this research, aged 6 to 24 months, showed normal nutritional status (74%). Furthermore, in the Kedungsari Health Center in Mojokerto Regency, there is a correlation between of breastfeeding and nutritional health in infants aged 6 to 24 months. This study's findings provide up-to-date information on the prevalence of exclusive breastfeeding, nutritional status, and the correlation between exclusive breastfeeding and nutritional status in babies aged 6 to 24 months.